Bactericidal Permeability Increasing Protein Deficiency Aggravates Acute Colitis in Mice by Increasing the Serum Levels of Lipopolysaccharide - Kong, Qingli; Lv, Zhe; Kang, Yun; An, Yunqing; Liu, Zhenlong; Zhang, Jianmin (Frontiers in Immunology, 2021)
Objective: The objective of this study was to understand the role of bactericidal permeability increasing protein (BPI) in the pathogenesis of experimental murine colitis. Methods: We used the Cre-LoxP system to generate BPI knockout（BPI KO） mice. Acute colitis was induced in BPI KO mice and wild-type (WT) mice by subjecting the mice to 5% dextran sulfate sodium (DSS). Mice were observed for symptoms of experimental colitis. The survival of BPI KO mice to infection with Acinetobacter baumannii, a gram-negative bacterium, was also assessed. Results: Southern blot, RT-PCR, and western blot results showed that the 2nd and 3rd exons of the murine Bpi gene were knocked out systemically, confirming successful construction of the BPI KO mouse. BPI KO mice subjected to DSS showed increased symptoms of experimental colitis, increased colonic mucosal damage, increased epithelial permeability, elevated levels of serum LPS, and a disrupted fecal microbiome as compared with WT mice. Furthermore, BPI KO mice challenged intraperitoneally with A. baumannii died sooner than WT mice, and the total number of bacteria in the abdominal cavity, spleen, and liver was increased in BPI KO mice as compared to WT mice. Conclusions: We successfully generated BPI KO mice. The BPI KO mice developed worse colitis than WT mice by increased colitis symptoms and colonic mucosal damage, elevated levels of serum LPS, and a disrupted microbiome. BPI could be a potential target for treatment of ulcerative colitis in humans.